2014
DOI: 10.1177/1541931214581010
|View full text |Cite
|
Sign up to set email alerts
|

Human-Machine Interface Development for Common Airborne Sense and Avoid Program

Abstract: Unmanned aerial systems (UAS) are starting to access manned airspace today and this trend will grow substantially as the number of UAS and their associated missions expand.A key challenge to safely integrating UAS into the National Airspace System (NAS) is providing a reliable means for UAS to sense and avoid (SAA) other aircraft. The US Air Force is addressing this challenge through the Common Airborne Sense and Avoid (C-ABSAA) program. C-ABSAA is developing a sophisticated "sense-and-avoid" capability that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In addition to range rings with adjustable display ranges, pilots were provided with either basic or advanced levels of information on the display to support their ability to maintain well clear. The basic display configuration contained a minimum set of intruder traffic information (Friedman-Berg et al, 2014;Draper et al, 2014;Fern et al, 2015). The intruder location, range, bearing, heading, relative altitude, vertical trend, heading predictor, and threat level were always visible to the pilots.…”
Section: Experimental Designmentioning
confidence: 99%
“…In addition to range rings with adjustable display ranges, pilots were provided with either basic or advanced levels of information on the display to support their ability to maintain well clear. The basic display configuration contained a minimum set of intruder traffic information (Friedman-Berg et al, 2014;Draper et al, 2014;Fern et al, 2015). The intruder location, range, bearing, heading, relative altitude, vertical trend, heading predictor, and threat level were always visible to the pilots.…”
Section: Experimental Designmentioning
confidence: 99%
“…The human factors researchers had to make the case to Special Committee 228 that the data from these human-in-the-loop simulations justified having the MOPS include information beyond the basic elements identified by Friedman-Berg et al (2014) and Draper et al (2014). Through presentations to the committee and working group meetings, the human factors researchers were successful in convincing the group to require maneuver guidance, which was the key addition provided by the advanced displays, as a minimum requirement.…”
Section: Should Advanced Information Elements Be Included? If So Howmentioning
confidence: 99%
“…A survey conducted by Draper, Pack, Darrah, Moulton, & Calhoun 12 , found that the majority of pilots surveyed indicated that the following information should be present at all times on a DAA display: intruder identification, intruder location, intruder relative position, intruder threat/alert level, DAA task priorities and status, DAA maneuver recommendations, flight restrictions, weather, navigation data, and visual alerts.…”
Section: Daa Displaysmentioning
confidence: 99%